2020
DOI: 10.1186/s12936-020-03501-4
|View full text |Cite
|
Sign up to set email alerts
|

From Plasmodium vivax outbreak to elimination: lessons learnt from a retrospective analysis of data from Guantang

Abstract: Background Malaria was once a serious public health problem in China, with Plasmodium vivax the major species responsible for more than 90% of local transmission. Following significant integrated malaria control and elimination programmes, malaria burden declined, and since 2017 China has not recorded any indigenous case. To understand the historical malaria transmission patterns and epidemic characteristics in China and insights useful to guide P. vivax malaria control and elimination elsewhere, a retrospecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“… 71 In accordance with this, studies from Ethiopia, 72 Kenya, 73 Tanzania, 74 and India 75 have revealed higher number of mosquito larvae in ponds and dams and higher malaria parasite prevalence among people living around such ponds and dams. Similarly, this finding conforms with the report of Yang et al 76 who reported a higher malaria infection among those who depend on unprotected water as a source of household water supply. Furthermore, children of household having stagnant water around their homes are four-fold likely to have malaria infection compared to their counterparts who do not have stagnant water around their homes.…”
Section: Discussionsupporting
confidence: 92%
“… 71 In accordance with this, studies from Ethiopia, 72 Kenya, 73 Tanzania, 74 and India 75 have revealed higher number of mosquito larvae in ponds and dams and higher malaria parasite prevalence among people living around such ponds and dams. Similarly, this finding conforms with the report of Yang et al 76 who reported a higher malaria infection among those who depend on unprotected water as a source of household water supply. Furthermore, children of household having stagnant water around their homes are four-fold likely to have malaria infection compared to their counterparts who do not have stagnant water around their homes.…”
Section: Discussionsupporting
confidence: 92%
“…However, before China's malaria control and elimination program was launched, a large number of malaria cases were observed during the non-transmission season (from February to April), which could be well explained by the first relapse episode of long-incubation cases. Previously, Yang and colleagues performed a descriptive analysis using historical monthly incidence data from the Henan province (central China) and observed clear double peaks of malaria episodes during the 1960s and 1970s further supporting our findings for both short-and long-period incubations [34].…”
Section: Discussionsupporting
confidence: 88%
“…sinensis, are preferentially zoophilic, 50 with an averaged preference ratio of 1:11.93 between humans and cattle. 51 Our results showed that Pipiserpin may be used to vaccinate animals to generate antisera, which would then be ingested when mosquitoes feed on these animals. Furthermore, the presence of undigested blood in the midgut may hinder a second round of blood feeding, which may help reduce mosquito populations.…”
Section: Discussionmentioning
confidence: 74%